2018
DOI: 10.18203/2394-6040.ijcmph20183859
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of prescribing skills among dental students in the eastern province, Saudi Arabia, University of Dammam

Abstract: Background: The objectives of the study were to assess knowledge and prescription skills of medications among dental student in Dammam University and evaluate the efficiency of an online application in improving their knowledge.Methods: A cross sectional pre-post study was conducted, a total of 96 students from 4th year to interns were enrolled. A formulated questionnaire was distributed to the students. An application that contained the most common drugs used in dentistry was made by the research team with he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The undergraduate students in Saudi universities usually learned the drug prescription in 2 pharmacological courses, however these courses are theoretical does not improve significantly the prescriptions skills of students. Therefore, dental students in this study showed higher level of prescription knowledge in comparison to prescription practices 11 . The present study, demonstrated a good prescription practices in higher percentage of internship students compared to other students.…”
Section: L-6mentioning
confidence: 62%
See 3 more Smart Citations
“…The undergraduate students in Saudi universities usually learned the drug prescription in 2 pharmacological courses, however these courses are theoretical does not improve significantly the prescriptions skills of students. Therefore, dental students in this study showed higher level of prescription knowledge in comparison to prescription practices 11 . The present study, demonstrated a good prescription practices in higher percentage of internship students compared to other students.…”
Section: L-6mentioning
confidence: 62%
“…The present study, demonstrated a good prescription practices in higher percentage of internship students compared to other students. Similarly, a study conducted in Dammam, Saudi Arabia, found a significant difference in practices of antifungal prescription between the internship students and other students 11 . The knowledge of students is expected to increase by the increase in educational level, and the dental practices are usually improved in internship year.…”
Section: L-6mentioning
confidence: 85%
See 2 more Smart Citations